Numerical modeling of thermomechanical behavior of semi-crystalline shape memory polymers - Golotina, Lyudmila Alexandrovna; Shardakov, Igor Nikolaevich (Computational Continuum Mechanics, 2011)
This paper is concerned with numerical modeling of a shape memory effect in semi-crystalline polymers. The shape memory effect is defined by a relaxation transition in the amorphous phase over a range of temperatures, including a glass transition temperature. Simulations are carried out using the variant of constitutive equations developed previously for describing thermomechanical behavior of semi-crystalline polymers over a wide temperature range and the kinetic equations for finding tensor quantities that characterize the evolution of intermolecular interactions. The results of numerical experiments obtained in modeling the thermomechanical cycle with unconstrained shape recovery for two pre-deformation states (uniaxial extension and uniaxial compression) are presented.
Keywords: semi-crystalline polymer; shape memory polymers; numerical modeling